2016
DOI: 10.1590/1806-9282.62.07.641
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of allogeneic stem cell transplantation among patients with acute myeloid leukemia presenting active disease: Experience of a single European Comprehensive Cancer Center

Abstract: OutcOmes Of allOgeneic stem cell transplantatiOn amOng patients with acute myelOid leukemia presenting active disease: experience Of a single eurOpean cOmprehensive cancer center rev assoC med bras 2016; 62 (7) Introduction: Allogeneic hematopoietic stem cell transplantation (ASCT) represents a potentially curative approach for patients with relapsed or refractory acute myeloid leukemia (AML). We report the outcome of relapsed/refractory AML patients treated with ASCT. Method: A retrospective cohort from 1994 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
0
0
1
Order By: Relevance
“…TRM was 47.6% in the same study. In our study relapse was observed in 10 of 31 patients (32.2%) during the first 90 days after transplantation, found to be similar (OS 7.9 months vs 8 months and PFS 3.5 months vs 3 months) (13).…”
Section: Discussionsupporting
confidence: 65%
“…TRM was 47.6% in the same study. In our study relapse was observed in 10 of 31 patients (32.2%) during the first 90 days after transplantation, found to be similar (OS 7.9 months vs 8 months and PFS 3.5 months vs 3 months) (13).…”
Section: Discussionsupporting
confidence: 65%
“…Infecções fúngicas estão mais relacionadas ao transplante alogênico que o autólogo, principalmente após o uso de corticosteroides e casos de DECH crônica. Esta última por sua contribuem para infecções de bactérias encapsuladas como Streptococcus pneumoniae ,Haemophilus influenzae e Neisseria meningitidis.14 O transplante de medula óssea alogênico vem sendo utilizado para o tratamento de portadores de HIV-AIDS, tanto para tentar uma cura da infecção, quanto por malignidades hematológicas que possam se apresentar nesses indivíduos.35 As complicações podem variar e estão muito relacionadas coma terapia anti-retroviral usada nesses pacientes, sendo mais comum as infecções oportunistas, viremias, cistites hemorrágicas, em alguns casos desenvolvimento de sarcoma de Kaposi, doença do enxerto contra o hospedeiro (DECH) e alterações hepáticas devido ao vírus da hepatite C.35 , recidiva da doença e mortalidade relacionada ao transplante elevada podem ser apresentadas por estes pacientes 36. O risco de morte pós o transplante alogênico tanto para LMA quanto para a Síndrome Mielodisplásica é alto, principalmente relacionada a doença do enxerto contra o hospedeiro e infecções virais e fúngicas 37.…”
unclassified